A Numerical-Taxonomic classification of Vitis spp and Cultivars Based on Leaf Characteristics - Swanepoel, J.J.; de Villiers, C.E. (South African Journal of Enology and Viticulture, 2017)
Grapevine leaves collected from three positions on the shoot during veraison were investigated for taxonomic characteristics. Numerical analyses were employed on 13 ampelographical and 13 morphological characteristics. Characteristics contributing to the variation between taxa were mainly quantitative. Although not clearly perceptible specimens tended to cluster in American (Vi tis spp and hybrids) and European (Vi tis vinifera) groups. Using the ampelographical characteristics hybrids tended to cluster with at least one of their parents.